Management of the Al Barqi Qur'an Learning Method at Darul Khair Foundation, Biting, Jember - Ahmad Nur Mahfuda (Faculty of Education and Teacher Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2023)
The Al-Barqy Management of Learning to Read the Qur’an Method is one of the excellent learning media for Qur'an educational institutions at the Darul Khair Foundation and the community around Biting Kab. Jember to improve the quality of a santri in reading the Qur'an. This research method uses a qualitative research method approach and the type of research uses descriptive qualitative, data collection uses observation, documentation, and interviews, while data analysis uses data reduction, data presentation, and data conclusion. Final research methodology to test the validity of using the Data Triangulation test. As for the results of his first research, the Al-Qur'an Learning Management used by the Darul Khair Foundation uses the Al Barqy Method with the application of letter recognition where the keywords are collected in sentences, namely: There is Raja, Maha Kaya, Katawana, sama laba. The 8-Hour System is learning to read the Qur'an Easily, Quickly, and never forgotten. The advantages of the al Barqy method with a pattern of 16 keyword letters and transfer letters. Learning the Al Barqy Method uses a Guidebook that has been written by the institution or KH. Muhadjir Sulthon and M. Romzul Islam Revised Edition. Supporting factors in the learning process involve students who already know the letters of the Qur'an, media in the form of Al-Barqy and Al-Qur'an modules, the Qur’an teacher or Ustad, and the Qur'an Education Curriculum